1992
DOI: 10.1002/ijc.2910500603
|View full text |Cite
|
Sign up to set email alerts
|

Human breast cancer: Concerted role of diet, prolactin and adrenal C19‐Δ5‐steroids in tumorigenesis

Abstract: The low incidence of breast cancer in Japan disappears within 2 generations in migrant Japanese in the USA. This is of fundamental importance if we are to understand, and perhaps reverse, the high rate seen in Western countries. Diet is the most likely factor involved, and a review of the topic of diet, body mass index, and gain in adult body mass, supports a relationship between these factors and breast-cancer risk in post-menopausal, but not pre-menopausal, women. A direct link between nutritional factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Low dopamine levels (associated with depression) also relieve dopamine’s suppressive effect on PRL secretion in the pituitary, thus perhaps compounding adverse effects on mood. Estrogen-induced cell proliferation is also part of the normal response of the pituitary and many other reproduction-related tissues 73,74. Estrogen exposures at the wrong levels or of inappropriate types can cause disregulated proliferation, and even produce tumors of those tissues,7577 including the pituitary;78 behavioral issues are compounded if these tumors are prolactinomas.…”
Section: Effects Mediated By Peptide Hormones Downstream Of Estrogensmentioning
confidence: 99%
“…Low dopamine levels (associated with depression) also relieve dopamine’s suppressive effect on PRL secretion in the pituitary, thus perhaps compounding adverse effects on mood. Estrogen-induced cell proliferation is also part of the normal response of the pituitary and many other reproduction-related tissues 73,74. Estrogen exposures at the wrong levels or of inappropriate types can cause disregulated proliferation, and even produce tumors of those tissues,7577 including the pituitary;78 behavioral issues are compounded if these tumors are prolactinomas.…”
Section: Effects Mediated By Peptide Hormones Downstream Of Estrogensmentioning
confidence: 99%
“…Certain groups of women—European/American versus Asian/African and high versus low calorie intake—may be at increased risk of breast cancer because of higher amounts of body fat, particularly during adolescence and postadolescence, and thereby higher aromatase and local estrogen formation 52, 78, 79 . Estradiol, estrone, and androstenediol are active estrogens that act in tumor initiation and/or growth of small tumors; when tumors are larger they may remain estrogen‐dependent or progress to estrogen‐independence 80 . The role of androgens per se in breast cancer development and growth is unclear 81 .…”
Section: Possible Role Of Dhea In Steroid‐dependent Human Cancersmentioning
confidence: 99%
“…In addition, limited estrogen-induced cell proliferation is part of the normal response of the pituitary but can also produce pituitary tumors (22). PRL is believed to be a growth factor for many tissues, including breast and prostate (23,24), so its overproduction or excessive release by estrogens could lead to pathologies or tumors of these target tissues (25). We have studied membrane-initiated, E 2 -induced mechanistic and functional actions in a rat pituitary tumor cell subline (GH3/B6) for several years, and we (26,27) recently demonstrated that representatives of another class of so-called weak estrogens (as defined via the genomic mechanism; environmental estrogens) can cause potent nongenomic signaling effects in these cells whenever the membrane estrogen receptor is expressed at high levels.…”
mentioning
confidence: 99%